Health, job characteristics, skills, and social and financial factors in relation to early retirement - results from a longitudinal study in the Netherlands - Astrid de Wind; Goedele A Geuskens; Jan Fekke Ybema; Birgitte M Blatter; Alex Burdorf; Paulien M Bongers; Allard J van der Beek (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: This study aimed to investigate the relative contribution of health, job characteristics, skills and knowledge, and social and financial factors to the transition from work to (non-disability) early retirement. METHODS: Employees aged 59-63 years (N=2317) were selected from the Study on Transitions in Employment, Ability and Motivation in the Netherlands (STREAM). Individual characteristics, health, job characteristics, skills and knowledge, and social and financial factors were measured using a questionnaire at baseline. Information on early retirement was derived from the one-year follow-up questionnaire. Logistic regression analyses were used to identify predictors of early retirement. Population Attributable Fractions (PAF) were calculated. RESULTS: Older age [odds ratio (OR) 1.79], poor physical health (OR 1.78), a positive attitude of the partner with respect to early retirement (OR 3.85), and the financial possibility to stop working before the age of 65 (OR 10.2) predicted the transition to early retirement, whereas employees that reported high appreciation at work (OR 0.58) and higher focus on development of skills and knowledge (OR 0.54) were less likely to retire early. PAF were 0.75 for the financial possibility to stop working, 0.43 for a positive attitude of the partner with respect to early retirement, 0.27 for low appreciation at work, 0.23 for a low focus on development, and 0.21 for poor health. CONCLUSIONS: The financial possibility to stop working before the age of 65 importantly contributes to early retirement. In the context of rapidly diminishing financial opportunities to retire early in the Netherlands, the prolongation of working life might be promoted by workplace health promotion and disability management, and work-related interventions focusing on appreciation and the learning environment.